The Analysis of Changes in Regional Pattern and Building Function of Gembongan Sugar Factory - Dita Ayu Rani Natalia; Akbar Preambudi; Annisa Nurul Lazmi (Universitas Bandar Lampung (UBL), 2022)
Java Island is one of the areas in Indonesia that has seen a rapid development of sugar factory industries during the 18th century. At that time, the existence of the factory was furthermore utilized by the Dutch colonial government to gain benefits. The location in which the sugar factory was built has been considered according to its surrounding potential. In addition, the sugar factory had facilities such as workers' settlements, management offices, convention halls, and medical clinics. Over time, changes in political and management of this industry have led to the cessation of production and the enclosure of the factory. Thus, the building has deteriorated with various damages. Through conservation, the building of a sugar factory is converted into a tourist facility that affects the condition of its surroundings. This research aims to study the development and changes that happen in the area of the sugar factory and the implications of its spatial pattern on the building function. This research utilizes qualitative methods with a deductive analysis approach that is based on chronological observation of photos, old maps, and spatial pattern changes from satellite images. The results show that there is a significant change related to function in the surrounding sugar factory caused by ownership factors.